How phase (α and γ) and porosity affect specific heat capacity and thermal conductivity of thermal storage alumina. Issue 3 (5th November 2020) - Huda, Nazmul; Whitney, Mark A.; Razmpoosh, Mohammad H.; Gerlich, Adrian P.; Wen, John Z.; Corbin, Stephen F.
Abstract: Ceramic materials are a potential medium to store thermal energy with a reasonable cost. Respective thermodynamic properties of ceramics generally depend on temperature, and the energy storage capacity significantly varies with microstructure and porosity of ceramics. In order to improve understanding on the correlation between microstructure change and energy storage capacity, two commercial grades of alumina specimens are characterized. Their thermo‐mechanical properties are measured and correlated with temperature‐dependent material phases (ie, α and γ phases) and porosity. Higher values of the γ phase fraction and the porosity result in a lower mass‐based specific heat capacity when the temperature changes from room temperature to 1200°C. On the other hand, lower values of the γ phase fraction and the porosity lead to higher values of thermal conductivity and diffusivity between room temperature and 900°C. While both alumina specimens exhibit a decrease in specific heat capacity with increasing temperature for temperatures above 590°C, largely due to the phase transformation from γ to α, they both exhibit a decrease in thermal conductivity with increasing temperature in the same range. Generally a sample with a higher fraction of α phase and a lower porosity possesses a higher thermal conductivity. Quantitative relations are derived from experimental data. Abstract : The graph represents, "How different microstructures of alumina and its phase transformation affect the specific heat capacity from room temperature to 1200°C".